Message from the Editor - (Editor), Prof.Dr. Hakan Sarı (Turkish International Journal of Special Education and Guidance & Counselling ISSN: 1300-7432, 2018)
Message from the Editor I am very pleased to publish second issue in 2018. As an editor of Turkish International Journal of Special Education and Guidance & Counselling (TIJSEG) this issue is the success of the reviewers, editorial board and the researchers. In this respect, I would like to thank to all reviewers, researchers and the editorial board. The articles should be original, unpublished, and not in consideration for publication elsewhere at the time of submission to Turkish International Journal of Special Education and Guidance & Counselling (TIJSEG), For any suggestions and comments on TIJSEG, please do not hesitate to send mail. Prof. Dr. Hakan Sarı Editor